THE EFFECT OF GROUP COUNSELING USING THE SOLUTION-FOCUSED BRIEF COUNSELING APPROACH ON ACADEMIC PROCRASTINATION BEHAVIOR AMONG STUDENTS AT TANJUNGANOM STATE HIGH SCHOOL 1, NGANJUK REGENCY - Endhang Maya Desiana; Dahlia Noviaring Asri; Tyas Martika Anggriana (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to determine the effect of group counseling services using the Solution-Focused Brief Counseling approach on the academic procrastination behavior of 12th-grade students at SMA Negeri 1 Tanjunganom, Nganjuk Regency, during the 2025/2026 academic year. This study employs a quantitative approach using a quasi-experimental method and a one-group pretest–posttest design. The research subjects consisted of 61 students with high levels of academic procrastination. The research instrument was an academic procrastination questionnaire developed based on indicators of delaying the start of tasks and avoiding academic tasks, and its validity and reliability had been tested. The data obtained were analyzed using descriptive and inferential statistics. The results of the normality test using the Shapiro–Wilk test indicated that the pretest and posttest data were not normally distributed; therefore, hypothesis testing proceeded with the Wilcoxon Signed-Rank Test. The analysis results showed a decrease in the average academic procrastination scores of students from the pretest to the posttest. The Wilcoxon test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between the pretest and posttest scores. Based on these findings, it can be concluded that group counseling services using the Solution Focused Brief Counseling (SFBC) approach significantly influence the reduction of students’ academic procrastination behavior. This study provides practical implications for guidance and counseling teachers to utilize the SFBC approach as an alternative intervention in helping students overcome academic procrastination, particularly at the high school level.